Relationships between the Cross Test and Other Balance Tests - MARUYAMA, Hitoshi; FUKUYAMA, Katsuhiko (Rigaku ryoho kagaku, 2010)
[Purpose] The purpose of this study was to clarify the relationships between the cross test and static balance as well as other dynamic balance test, and examine the sway path plots obtained in the cross test. [Subjects] The subjects were 73 students attending a vocational training college. [Method] Using measurement of center of gravity sway, we measured static standing balance with the eyes open and closed, and in one-leg standing, and performed the cross test and functional reach test. Then, we investigated the relationships among them. [Results] We found correlations among static standing balance with eyes open and closed and one-leg standing. No correlation was found between the cross test parameters and any of the other measured parameters, but correlations were found between the rectangular area minus the circumferential area of the sway path obtained in the cross test and static standing balance with eyes open and closed. [Conclusion] Many factors, including static balance, contribute to the parameters of the cross test, however the results suggest the possibility that the outline of the sway path plot reflects the static balance.